2001
DOI: 10.1007/s001340000799
|View full text |Cite
|
Sign up to set email alerts
|

Is a short trial of prone positioning sufficient to predict the improvement in oxygenation in patients with acute respiratory distress syndrome?

Abstract: A short-term trial of prone positioning does not appear a sufficient method to identify patients who would benefit from the postural treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 15 publications
2
21
0
3
Order By: Relevance
“…2,3,24,56,80,81,101 Of the observational studies reviewed that measured P aO 2 /F IO 2 , the mean increase ranged from 21 to 161 mm Hg (19 -168% improvement). 26,27,[29][30][31][32][33]36,37,82,[84][85][86][87][88][89][90][91][92][93][94][95][96][97]42,103,105,108 The magnitude of improvement in P aO 2 /F IO 2 among morbidly obese subjects versus nonobese subjects with ARDS was found to be significantly greater (104 mm Hg vs 61 mm Hg, respectively, P ϭ .04) and was also observed in a larger proportion of subjects (77% vs 50%, respectively, P ϭ .044). 105 Similar positive responses also have been reported in subjects without ARDS, where the mean P aO 2 /F IO 2 increase was from 39 -192 mm Hg (24 -267% improvement).…”
Section: Magnitude Of Oxygenation Responsementioning
confidence: 88%
See 4 more Smart Citations
“…2,3,24,56,80,81,101 Of the observational studies reviewed that measured P aO 2 /F IO 2 , the mean increase ranged from 21 to 161 mm Hg (19 -168% improvement). 26,27,[29][30][31][32][33]36,37,82,[84][85][86][87][88][89][90][91][92][93][94][95][96][97]42,103,105,108 The magnitude of improvement in P aO 2 /F IO 2 among morbidly obese subjects versus nonobese subjects with ARDS was found to be significantly greater (104 mm Hg vs 61 mm Hg, respectively, P ϭ .04) and was also observed in a larger proportion of subjects (77% vs 50%, respectively, P ϭ .044). 105 Similar positive responses also have been reported in subjects without ARDS, where the mean P aO 2 /F IO 2 increase was from 39 -192 mm Hg (24 -267% improvement).…”
Section: Magnitude Of Oxygenation Responsementioning
confidence: 88%
“…Regardless of ARDS classification, the typical response is rapid initial improvement in oxygenation (ie, Ͻ 30 min), followed by a more gradual increase over an extended, variable time frame. In both ARDS p and ARDS exp , Papazian et al 86 reported that 73% of responders to PP exhibited a fast (1 h) improvement in P aO 2 /F IO 2 , whereas 27% were characterized as slow responders, requiring 6 h. In ARDS p , Langer et al 80 Steady oxygenation improvements over a prolonged time course have been a consistent feature of many studies. In trauma-associated ARDS, Fridrich et al 24 found an immediate increase in P aO 2 /F IO 2 with continued improvement over 20 h. Likewise, in ARDS associated with severe burns, Hale et al 94 observed that mean P aO 2 /F IO 2 increased almost immediately after placement in PP (from 87 to 133 mm Hg) and improved steadily until reaching a peak of 236 mm Hg at 36 h. Reutershan et al 92 described both subjects whose oxygenation plateaued early (2-4 h) and those with continual improvement over 8 h. Stocker et al 27 observed subjects who required up to 24 h before oxygenation improved.…”
Section: Temporal and Etiological Aspects Of Oxygenation Responsementioning
confidence: 91%
See 3 more Smart Citations